The role of need satisfaction for solo self-employed individuals' vs. employer entrepreneurs' affective commitment towards their own businesses - Steffen E. Schummer; Kathleen Otto; Lena Hünefeld; Maria U. Kottwitz (Journal of Global Entrepreneurship Research, 2019)
Persistence in self-employment is crucial for entrepreneurial activities to generate long-term economic benefits. Consequently, this research examined the commitment of the self-employed towards their business as an important determinant of persistence. However, this research treats the self-employed as one entity. Yet we assume that especially for the research on commitment the differentiation of the self-employed into solo self-employed individuals (self-employed individuals without employees) and employer entrepreneurs (self-employed individuals with employees) provides seminal insights. Thus, this study examined differences in affective commitment to (emotional attachment to and identification with) one's business and its antecedents between these self-employment forms. We used data of German solo self-employed individuals (n = 117) and employer entrepreneurs (n = 103) from the European Working Condition Survey (EWCS 2010). A simple t test revealed that the solo self-employed individuals report lower levels of affective commitment to their business than employer entrepreneurs. Moreover, regression analyses revealed that satisfaction of the needs for autonomy and competence was more strongly related to affective commitment for the solo self-employed than that for employer entrepreneurs, whereas satisfaction of the need for relatedness was more weakly related among the solo self-employed than that the employer entrepreneurs. These results suggest that solo self-employed individuals and employer entrepreneurs not only differ in affective commitment to their businesses but also in their antecedents. Implications for research on motivational processes of the self-employed and for fostering persistence in self-employment are discussed.
Keywords: 650; Entrepreneurship; Small business owners; Self-employment; Social identity; Self-determination theory; Need satisfaction; Autonomy; Competence; Relatedness; Affective commitment